Potensi, Peluang, Dan Tantangan Perdagangan Antara Indonesia Dengan Negara-Negara Di Kawasan Timur Tengah - Sudirman, Sudirman (Al-Buhuts, 2016)
This study aims to assess the potential, opportunities, and challenge of trade between Indonesia and countries in the middle east. It is qualitative research by using descriptive method. The data is used mainly secondary data, it drawn from relevant institutions, among others: industry and trade, chamber of commerce, the Central Bureau of Statistics, and of the documents related. This study found a variety of potentials, opportunities, and challenges of trade between Indonesia and countries in the middle east, namely: 1) the potential, among other things: the products produced in Indonesia tend to be different from the product produced in the countries middle east region countries, economic growth in the countries of the Middle east are relatively stable. Indonesia has export commodity that was diverse, the competitiveness of Indonesian products is quite high, and the growth of foreign capital in the countries of the Middle East are likely to increase. 2) opportunities, among others: change in economic policy-oriented market economy, relations bilateral diplomacy between Indonesia and countries in middle east has been good, the equation beliefs, it discourse will do the trade in free trade Indonesia between Morocco and Turkey. 3) challenges, among others: Long distance, tariffs are high, less stable political climate, limited support of the financial institutions sector, unavailability of halal certification bodies are gaining international legitimacy.